2010
DOI: 10.1007/s10705-010-9373-5
|View full text |Cite
|
Sign up to set email alerts
|

Soil phosphorus distribution in sequentially extracted fractions in tropical coffee-agroecosystems in the Atlantic Forest biome, Southeastern Brazil

Abstract: Phosphorus (P) deficiency is one of the most important constraints to food production, particularly in tropical Oxisols. This study aimed to characterize the inorganic and organic P (Pi and Po) fractions in the soil in three smallholding coffee cultivation fields managed under either agroforestry (AGF) or full sun (FSC) agroecosystems. The work was carried out in areas situated at the municipalities of Divino and Araponga in the Zona da Mata in the state of Minas Gerais, southeastern Brazil. Soil P forms inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 30 publications
2
13
1
1
Order By: Relevance
“…This proportion of Po is within the range found in tropical regions for several soil orders (from low to medium content of organic C) and land-use systems, with average values of total Po from 26% [9,35,36] to 31% [11,19,37]. Oliveira et al [38] found proportions of total Po ranging from 36% to 46% for soils with high contents of organic matter, a conclusion that supports these findings.…”
Section: Distribution Of Organic and Inorganic P Fractionssupporting
confidence: 70%
“…This proportion of Po is within the range found in tropical regions for several soil orders (from low to medium content of organic C) and land-use systems, with average values of total Po from 26% [9,35,36] to 31% [11,19,37]. Oliveira et al [38] found proportions of total Po ranging from 36% to 46% for soils with high contents of organic matter, a conclusion that supports these findings.…”
Section: Distribution Of Organic and Inorganic P Fractionssupporting
confidence: 70%
“…It is possible that the ignition method underestimated total P, although it yielded similar total P concentrations in a range of soils from central Panama to the H 2 O 2 -H 2 SO 4 procedure used here to determine residual P (Turner and Engelbrecht 2011). Here, the HCl strong fraction was a much larger percentage of occluded P (HCl strong P plus residual P = 88% of the total P in surface soil) than the values of 36-55% reported for other strongly weathered soils (Lilienfein et al 2000;Xavier et al 2011). We therefore suspect that the HCl strong extract overestimated P in that fraction.…”
Section: Differences Among Fractionsmentioning
confidence: 47%
“…Phosphorus, the second most widely limiting nutrient in soil after nitrogen (Balemi and Negisho 2012), is a critical macronutrient for plant growth; and in tropical agroecosystems soil, P deficiency is a major limitation to crop production (Mustonen et al 2012). Research report indicate that <1 % of soil P is available for plant uptake (Stewart and Tiessen 1987) as a result of strong adsorption of phosphate by iron and aluminium oxides (Xavier et al 2011). According to Sharma et al (2011), phosphorus has a significant role in sustaining and building up soil fertility, especially under intensive system of agriculture.…”
Section: Introductionmentioning
confidence: 99%